2012
DOI: 10.1590/s0004-28032012000200010
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of alpha interferon (+ ribavirin) in the treatment of chronic viral hepatitis C genotypes 2 and 3 in a brazilian sample

Abstract: IntroductIonChronic hepatitis C represents a major public health problem worldwide. The estimated average global prevalence is close to 3% (ranging from 0.1% to 5% in different countries). Therefore, there are about 175 million carriers of hepatitis C virus (HCV) worldwide (24) . Approximately 30% of infected patients develop cirrhosis in 20-30 years and 1%-4% are considered at high risk of developing hepatocellular carcinoma (23) . The chronicity of hepatitis C is characterized by persistent HCV for 6 months.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…SVR was seen in 30 of 50 patients (60%). In a study performed by Goncalves et al (12) with 141 patients, ETVR and SVR were found in 77 (54.6%) and 56 (39.7%) patients. In our study, SVR rates were similar to those in the literature.…”
Section: Discussionmentioning
confidence: 91%
“…SVR was seen in 30 of 50 patients (60%). In a study performed by Goncalves et al (12) with 141 patients, ETVR and SVR were found in 77 (54.6%) and 56 (39.7%) patients. In our study, SVR rates were similar to those in the literature.…”
Section: Discussionmentioning
confidence: 91%
“…23,24 Tais casos podem, desde que bem monitorados clinicamente, aguardar os resultados de pesquisas sobre fármacos de efeitos mais promissores e menos deletérios. Gonçalves e colaboradores 25 acompanharam 141 pacientes em tratamento da hepatite C crônica e verificaram, entre os eventos adversos mais frequentes, fadiga, cefaleia e mialgia, além de terem observado 13 interrupções de tratamento por eventos adversos, dos quais 9 foram considerados eventos adversos graves. O tratamento de pacientes com alterações arquiteturais menores também implica gastos desnecessários para o sistema de saúde.…”
Section: Discussionunclassified
“…It constitutes an unexpected and stressful event, which may engender feelings of fear, denial, grief, anger, sadness, and stigma. Since hepatitis C is a frequently-asymptomatic and slowlyevolving chronic disease, it is the diagnosis itself that causes patients to realize they are sick, which is further corroborated when the first adverse side effects of treatment set in [6,9].…”
Section: "Becoming Sick" Because Of the Treatment: Perceived Aspectsmentioning
confidence: 99%